2022
DOI: 10.1111/ans.17463
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of primary site adjuvant radiotherapy following transoral robotic surgery: a cohort study

Abstract: Background: Post-operative radiotherapy (PORT) volumes and dose to target structures likely influence swallowing function and quality of life following transoral robotic surgery (TORS). The aim of this study is to analyse disease control and swallowing outcomes in patients undergoing TORS for oropharyngeal squamous cell carcinoma (OPSCC) to determine the impact of omitting the primary site from the PORT treatment volume. Methods: Prospectively collected data from patients that underwent TORS between March 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The recurrence of OPSCC after TORS was analyzed by subsite in 13 studies [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. There was no statistically significant difference in the odds of total recurrence between tonsillar and BOT OPSCC (1.1 [95%CI 0.8–1.5], p = 0.480) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence of OPSCC after TORS was analyzed by subsite in 13 studies [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. There was no statistically significant difference in the odds of total recurrence between tonsillar and BOT OPSCC (1.1 [95%CI 0.8–1.5], p = 0.480) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…As radiotherapy or chemoradiotherapy has been supported for tumors with positive margins [ 76 , 77 ], these treatments may have influenced the nonsignificant differences in locoregional and distant control seen between tonsillar and BOT OPSCC, even though BOT OPSCC had higher rates of positive margins. Only two studies reported differences in adjuvant therapy between subsites, with Fradet et al finding no differences in the rate of adjuvant therapy, whereas Persky et al found that BOT OPSCC underwent more chemoradiation secondary to more positive margins [ 12 , 40 ]. In looking at all the subsites combined, a few studies have endorsed TORS with adjuvant therapy to be superior to TORS alone, particularly when considering locoregional control [ 16 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the senior author has never used jejunal flaps, gastro‐omental free flaps were used for early in this series for chemoradiation failures, but in the last 7 years, fasciocutaneous flaps have been used exclusively for laryngopharyngeal reconstruction. In contrast, human papilloma virus induced oropharyngeal cancers are now the most common mucosal cancer 13 . The rising incidence combined with TORS has increased the need for oropharyngeal reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, human papilloma virus induced oropharyngeal cancers are now the most common mucosal cancer. 13 The rising incidence combined with TORS has increased the need for oropharyngeal reconstruction. Whilst most TORS cases do not require a free flap, ALT and radial forearm flaps have been used to reconstruct both post-radiation recurrences, usually via mandibulotomy, and tonsil cancers that extend into the soft palate, via TORS, to prevent velopharyngeal insufficiency.…”
Section: Flap Selectionmentioning
confidence: 99%